El tratamiento - Hayder, Mo (Nuevos tiempos (Madrid, Spain), 2014)
Detective Jack Caffery returns to investigate a brutal attack on a London couple and the mysterious disappearance of their young son, a crime that brings him face to face with nightmarish memories of his own past.